2015
DOI: 10.1186/s13584-015-0055-2
|View full text |Cite
|
Sign up to set email alerts
|

Family history intake: a challenge to personalized approaches in health promotion and disease prevention

Abstract: BackgroundFamily history is considered an essential, obligatory part of the primary physician’s intake interview. Including coded FH in a unified medical file can save expensive genetic tests and detect the early onset of diseases in young people who are not recommended to be screened routinely. The objectives of this study are to explore the frequency and point in time of recording the coded family history (FH) as a first step to increasing awareness of the importance of such information.MethodsAll ICD-9 code… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…None of the 6 individuals with the HOXB13 c.251G>A variant reported family or medical history of prostate cancer. Cardiovascular diseases, hypertension, and diabetes were the most frequent family history documentation in the health system (37). From our data, the fraction of genotype and phenotype associations from family history ranged from 24 to 57% in dyslipidemia, cardiomyopathy and arrhythmia, diabetes, and endocrine diseases, and our deep phenotype tests detected clinical and preclinical presentations, further enhancing the clinical diagnosis of genetic disorders in adults (Fig.…”
Section: Discussionsupporting
confidence: 51%
“…None of the 6 individuals with the HOXB13 c.251G>A variant reported family or medical history of prostate cancer. Cardiovascular diseases, hypertension, and diabetes were the most frequent family history documentation in the health system (37). From our data, the fraction of genotype and phenotype associations from family history ranged from 24 to 57% in dyslipidemia, cardiomyopathy and arrhythmia, diabetes, and endocrine diseases, and our deep phenotype tests detected clinical and preclinical presentations, further enhancing the clinical diagnosis of genetic disorders in adults (Fig.…”
Section: Discussionsupporting
confidence: 51%
“…This is a relatively high frequency of recording when compared with similar research, other than one study which found 97% of EMRs contained FH information. 19 Two recent studies found that 12% and 56.6% of primary care records contained FH information respectively, 10 , 32 although the comparisons are limited by the differing settings. In the most comparable general/family practice setting, Rafi et al found 39.3% of EMRs contained FH information.…”
Section: Discussionmentioning
confidence: 99%
“…Similar methodology had been employed in previous studies. 10 , 19 , 23 We defined our own three discrete measures to subcategorize the standard of FH recording. The frequency of FH recording, how often any FH information was recorded—positive or negative.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Self-reported histories can be limited, inaccurate, or static. 11,12 Patients often relay information in an unprepared manner during an office visit. 13 Physicians admit they lack the knowledge to assess risk for diseases based on family history.…”
Section: Introductionmentioning
confidence: 99%